Experiential Marketing: Managing Tourist Satisfaction and Revisit Intention With Moderating Effects of Gender - kristiningsih; Soebandhi, santirianaingrum; trimarjono, adrianto (Jurnal Bisnis dan Manajemen, 2025)
This research aims to explore the correlation among experiential marketing, customer satisfaction, and the likelihood of customers returning in Indonesia. Additionally, the study also examines whether gender acts as a significant moderator in the relationship between these variables. The Surabaya municipal council aims to reopen the popular tourist location as a place to enjoy dining and shopping. The landmark has long been regarded as a symbol of the city. Regrettably, as time passes, it loses popularity. A better understanding of this issue can aid local businesses and municipal government in enhancing Surabaya’s tourism and culinary industries, particularly those in the place. We distributed questionnaires via online surveys, and 154 data sets that might be further examined were gathered. Except for the influence of gender as a moderator in the relationship between experiential marketing and customer satisfaction, our analysis confirms the validity of all hypotheses